Understanding of supramolecular solution polymerization and interfacial polymerization via forming multiple hydrogen bonds: a computer simulation study. Issue 29 (13th July 2022) - Shi, Meng-Yu; Li, Chu-Xiang; Song, Wen-Yuan; Liu, Hong; Xue, Yao-Hong; Wang, Yan
Abstract : We have conducted a detailed simulation study of supramolecular solution polymerization as well as interfacial polymerization employing a coarse-grained model which is closer to the real monomer structure via computer simulations. Abstract : By employing dissipative particle dynamics (DPD) simulations combined with stochastic polymerization models, we have conducted a detailed simulation study of supramolecular solution polymerization as well as interfacial polymerization employing a coarse-grained model which is closer to the real monomer structure. By adding bending angle potentials to coarse-grained models representing supramolecular reactive monomers, we achieved monomer model simulations for different kinds of multiple hydrogen bonds. Our simulation results indicated that for the interfacial polymerization system, the volume of the monomer caused a strong steric hindrance effect, which in turn led to a low average degree of polymerization of the product. Therefore, by appropriately reducing the volume of the reaction monomer (corresponding to different confinement ascribed to the multiple hydrogen bonds), the average polymerization degree, the degree of reaction and the polymerization rate of the monomer can be effectively improved. For the solution polymerization system and the interfacial polymerization system, a certain proportion of rigid monomers and flexible monomers (60% rigid monomers and 40% flexible monomers) are mixed. High molecular weight products can thus be obtained via the polymerization reaction. The simulation strategy proposed in this study can not only provide theoretical guidance for better design of new supramolecular systems, but also provide ideas for the further synthesis of higher molecular weight supramolecular polymers.